Identification of Learning Implementation of Civics Teachers in The Formation of Students' Nationalist Character Junior High School Advent Abepura - Mawara, Ricky Engel; Kulyasin, Kulyasin (ITScience (Information Technology and Science), 2024)
Civics is a subject related to recitations of the 1945 Constitution, Pancasila, and ceremonies. In fact, Civics is an educational program in which the core is political democracy, and the output is a good and intelligent citizen living according to the goals of the state, becoming a citizen who is aware of his rights and obligations, as well as a nationalist citizen or love for the country. The results of the study aim to describe the analysis of the implementation of Civics teacher learning in the formation of the nationalist character of Adventist Abepura Junior High School students. The method in this research is qualitative, combined with a descriptive approach. The data collection process was carried out through observation, interviews, and documentation. The results showed that the formation of the character of nationalism at Adventist Junior High School Abepura is not simple, especially since the majority of students are native Papuans. Various obstacles, namely a very different history, significantly in relation to the Netherlands compared to other regions in Indonesia. Second, there have been ongoing political tensions since integration into the Republic of Indonesia. Third, there are problems with the implementation of special autonomy policies and the use of special autonomy funds. The approach to conflict must be improved, even if it does not instantly solve the problem. At least, the pattern of violence should be reduced slowly in order to meet the same intersection for an act of peace.